2023
DOI: 10.1177/10711007231175846
|View full text |Cite
|
Sign up to set email alerts
|

The Role of First Tarsometatarsal Joint Morphology and Instability in the Etiology of Hallux Valgus: A Case-Control Study

Abstract: Background: The morphology of foot joints is widely accepted as a significant factor in the development of various foot disorders. Nevertheless, the role of the first tarsometatarsal joint (TMT1) morphology in hallux valgus (HV) remains unclear, and its impact on TMT1 instability has not been fully explored. This study aimed to investigate the TMT1 morphology and its potential correlation with HV and TMT1 instability. Methods: Weightbearing computed tomography (WBCT) scans of 82 consecutive feet with HV and 79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The current study of Ji et al 4 exemplifies well the opportunities provided by WBCT imaging for the utilization of both 2D (represented by the sagittal plane 1stTMT angle) and proper 3D assessments (represented by the shape modeling reconstruction of the anatomy of the proximal aspect of M1) in HVD patients. The authors should be commended for taking one step further in the long pathway to understanding HVD in a 3D environment.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…The current study of Ji et al 4 exemplifies well the opportunities provided by WBCT imaging for the utilization of both 2D (represented by the sagittal plane 1stTMT angle) and proper 3D assessments (represented by the shape modeling reconstruction of the anatomy of the proximal aspect of M1) in HVD patients. The authors should be commended for taking one step further in the long pathway to understanding HVD in a 3D environment.…”
supporting
confidence: 63%
“…This traditional assessment limits the 3D interpretation of the deformity and the multiple involved factors, such as the rotational profile of the first ray, metatarsal-sesamoid interaction, and anatomical characteristics of bones and joints. The study by Ji et al 4 in the current issue of FAI supports the critical transition from a 2D to a 3D assessment of HVD. The authors compared anatomical features of the first tarsometatarsal joint (1stTMTJ), particularly the shape of the articular surface of the proximal first metatarsal (M1), between HVD patients and controls using weightbearing CT (WBCT) imaging and 3D bone modeling.…”
mentioning
confidence: 51%
“…From individual articles, both Kimura et al (2017) and Lee et al (2022) found significantly larger TMT angles (sagittal view) on WBCT in patients with HV compared to healthy patients without HV (p < 0.01 and p < 0.001, respectively) [14,36]. Likewise, Ji et al (2023) reported a significantly larger TMT angle (sagittal view) in patients with HV as compared to healthy patients without HV on WBCT (1.6 versus 0.9 degrees; p < 0.01) [27]. From a different view, Randich et al (2021) reported a TMT angle (frontal view) on WBCT of −5.36 ± 6.28 degrees in patients with HV as compared to −1.28 ± 6.33 degrees in healthy patients without HV (p = 0.08) [40].…”
Section: Midfoot Instability Via Tarsometatarsal Anglementioning
confidence: 96%
“…Refer to Table 2 for more specific information on the demographics and patient information for each individual included in the article. 2023) reported significantly greater IMT angles (axial view) on WBCT in patients with HV as compared to healthy patients without HV (p < 0.001 and p < 0.01, respectively) [14,27]. The frequencyweighted mean TMT angle (axial) on WBCT was 15.4 ± 1.0 degrees for patients with HV (n = 112 feet) and 8.6 ± 0.5 degrees for healthy patients without HV (n = 109 feet).…”
Section: Severity Of Hallux Valgus By Imagingmentioning
confidence: 98%
“…Ji et al 8 used weight-bearing CT scans to compare the first tarsometatarsal joint (TMT1) morphology between 82 feet with hallux valgus and 79 controls. Multiple radiographic parameters differed significantly between the 2 groups, including the middle facet width, inferior lateral facet height and angle, and the TMT1 angle (p < 0.05).…”
Section: Forefootmentioning
confidence: 99%